Luminescence chronology of fluvial and aeolian deposits from the Emirate of Sharjah, UAE. (March 2023) - Mueller, Daniela; Raith, Kira; Bretzke, Knut; Fülling, Alexander; Parker, Adrian G.; Parton, Ash; Preston, Gareth W.; Jasim, Sabah; Yousif, Eisa; Preusser, Frank
Abstract: Quaternary environments on the Arabian Peninsula shifted between pronounced arid conditions and phases of increased rainfall, which had a profound impact on Earth surface processes. However, while aeolian sediment dynamics are reasonably well understood, there is a lack of knowledge with regard to variability in the fluvial systems. Presented here are the findings from several locations within wadi drainage systems to the west of the Hajar Mountains (United Arab Emirates). The performance of optically stimulated luminescence dating using a customized standardized growth curve approach is investigated, showing that this approach allows reliable determination of ages by reducing the machine time required. Three main periods of fluvial activity occurred at 160–135, 43–34, and ca. 20 ka. Additional ages fall into the latest Pleistocene and Late Holocene. None of the ages coincides with major wet periods in SE Arabia that have been identified in stalagmites and by the deposition of lake sediments. It is shown that fluvial activity was partly contemporaneous (within the given time resolution) with phases of aeolian deposition and was almost continuous, but likely sporadic, during the Middle to Late Pleistocene. This highlights the need for regionally defined paleoenvironmental records to fully understand the response of dryland systems to long-term climatic change.